Role of endogenous nitric oxide on PAF-induced vascular and respiratory effects - M. Clement; M. Albertini (Mediators of Inflammation)
The role of endogenous nitric oxide (NO) on vascular and respiratory smooth muscle basal tone was evaluated in six anaesthetized, paralysed, mechanically ventilated pigs. The involvement of endogenous NO in PAF-induced shock and airway hyperresponsiveness was also studied. PAF (50 ng/kg, i.v.) was administered before and after pretreatment with NG-nitro-L-arginine methyl ester (L-NAME, 10 mg/kg, i.v.), an NO synthesis inhibitor. PAF was also administered to three of these pigs after indomethacin infusion (3 mg/kg, i.v.). In normal pigs, L-NAME increased systemic and pulmonary vascular resistances, caused pulmonary hypertension and reduced cardiac output and stroke volume. The pulmonary vascular responses were correlated with the increase in static and dynamic lung elastances, without changing lung resistance. Inhibition of NO synthesis enhanced the PAF-dependent increase in total, intrinsic and viscoelastic lung resistances, without affecting lung elastances or cardiac activity. The systemic hypotensive effect of PAF was not abolished by pretreatment with L-NAME or indomethacin. This indicates that systemic hypotension is not correlated with the release of endogenous NO or prostacyclines. Indomethacin completely abolished the PAF-dependent respiratory effects.